Voices from the ghetto of Thessaloniki: mother–son correspondence as a source of Jewish everyday life under persecution#. Issue 2 (3rd April 2017) - Saltiel, Leon
Abstract: The article discusses the content of 52 letters written by three different Jewish mothers living in the ghetto of Thessaloniki and sent to their sons, all residing in Athens, during the Second World War. This unique find can shed light on the lives of ordinary Jewish citizens in the ghetto of Thessaloniki, never before known in such a detail. The information presented in these letters is invaluable. These eyewitness accounts describe the general situation and the emotions right before and during the deportations, which is when these letters stop. Other than narrating some of the major events of this period, the reader learns details ranging from family and inter-communal relations, to the daily nutrition, diseases and the price of different goods. Last but not least, they provide a window into the daily life during the German occupation in Thessaloniki, free from hindsight.